Child-headed households in Rakai District, Uganda: a mixed-methods study. (2nd January 2016) - Collins, Lisa; Ellis, Matthew; Pritchard, Edward W. J.; Jenkins, Christopher; Hoeritzauer, Ingrid; Farquhar, Adam; Laverty, Orla; Murray, Vincent; Nelson, Brett D.
Abstract : Objective: An important but neglected consequence of the AIDS pandemic that continues across sub-Saharan Africa is the phenomenon of child-headed households (CHH). This study aims to describe the challenges to health and well-being for young people living in child-headed households. Methods: A mixed-methods research approach linked common themes using qualitative and quantitative instruments to provide a broad picture of the location and challenges of CHH in Kabira, Kyotera and Kamuganja in the Rakai District of southern Uganda. Local knowledge was used to locate CHH. Results: 163 children living in 40 CHH were traced: 42·5% of the household heads were double orphans caring for younger siblings, and 43% were also caring for chronically ill or disabled grandparents who were economically unproductive and largely dependent on the eldest child for survival. It was found that those heading households were more likely not to attend school than children living at home with a parent. Their immediate needs ranged from food and shelter to health-care and education. Fear was a major theme: 38% of those interviewed reported fear of 'violence'. Children as young as 13 were responsible for navigating through complex decision-making processes from everyday basic necessities to decisions on the health care of younger siblings and grandparents. Conclusion: Children and young people living in CHH are a largely invisible and highly vulnerable population. Clear, officially accepted definitions of CHH are a first step in recognising this vulnerable group for whom safeguards will be necessary as social work develops in lower- and middle-income countries (LMICs). The precise numbers of CHH are unknown and further examination of this undocumented group is needed.